Primary alveolar rhabdomyosarcoma of the diaphragm requiring proximal gastrectomy - Yuki Mizuno; Naoki Shimojima; Atsushi Makimoto; Yuichi Yokokawa; Kazuaki Miyaguni; Ayano Tsukizaki; Makoto Hashimoto; Miki Ishikawa; Hideo Ishihama; Hirofumi Tomita; Akihiro Shimotakahara; Yuki Yuza; et al. (Elsevier, 2022)
Primary rhabdomyosarcoma (RMS) of the diaphragm, especially alveolar RMS, is extremely rare. Because of its rarity, no treatment for it has yet been established, but previous studies have reported long-term survival in recipients of a combination therapy with local control, including a total resection and/or radiation therapy concomitant with multiagent chemotherapy. We experienced a case of primary alveolar rhabdomyosarcoma of the diaphragm surrounding the gastric cardia in a 15-year-old, female patient. After administering chemotherapy consisting of vincristine, actinomycin D, and cyclophosphamide (VAC) to shrink the tumor, tumor resection was performed with a proximal gastrectomy and partial resection of the diaphragm, pericardium, and left lung. After receiving postoperative adjuvant chemotherapy with VAC and radiotherapy at a total of 41.4 Gy, the patient has been relapse-free for 18 months. The tumor-induced stenosis at the hilum was corrected, allowing oral intake and markedly improving the patient's nutritional status. Tumor resection with a proximal gastrectomy for primary diaphragmatic RMS surrounding the lower esophagus is recommended both for its efficacy in local control and for allowing the preservation of postoperative gastrointestinal function.